Changing Cuba: a double challenge - Grabendorff, Wolf (2017)
The article contains an analysis of the peculiar development by which Cuba has gone through. It has certainly depended on external factors. Because of geopolitical or economic interests, since its Revolution, Cuba has suffered constant international intervention. Time after, the construction and survival of a post-revolutionary economic and social model, depended on the support or the “abandonment” of the major actors during the period of the Cold War. Now, almost 60 years after the Cuban Revolution, still the remittances from abroad, constitute the most significant income to Cuba. In this context, now Cuba has a double challenge: to achieve an economic and political reform, and its reintegration to the American Continent.